Prevalence of Forward Head Posture and Its Association with Smartphone Use among University Students: Prevalence of Forward Head Posture and Association with Smartphone Use - Saeed, Ayesha; Shahed, Aimen; Liaqat, Maria; Farhat, Rameen; Khursheed, Rija; Ahmed, Safeer; Rafique, Nazish; Rafique, Anum (Pakistan BioMedical Journal, 2024)
A person exhibits forward head posture when their spine is out of neutral alignment with their head. Nowadays, smartphones are a necessary tool whose use is becoming increasingly significant. The side effect of smartphone use is forward head posture, which is most common among university students. Objectives: To determine the prevalence of forward head posture and its association with smartphone use among university students. Methods: This correlational study was conducted on university students with a sample size of 340. Both male and female students aged between 18-28 years, who use their smartphones for at least four hours and have no previous record of birth defects of cervical and lumber vertebrae were included. Whereas, any history of cervical surgery, or spinal abnormalities was excluded from the study. The goniometer and ruler method were used to measure the craniovertebral angle, and a smartphone addiction scale was used to screen the participants. Results: A positive correlation was found between craniovertebral angle and duration of smartphone usage with a correlation coefficient of r=0.084 and p=0.02. In contrast, a negative correlation was observed between the ruler method and the duration of smartphone usage with a correlation coefficient of r=0.54 and p=0.403. Conclusions: It was concluded that the prevalence of forward head posture was found to be 47.9% by the ruler method and 62.1% by the craniovertebral angle measurement. There is a correlation between craniovertebral angle and smartphone use and the duration of smartphone usage.